(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
The COVID-19 pandemic brought to the scene new questions about extension practice onto the scene. In the case of the extension project "El Sur También Publica", the question arose about sustaining the activity that year after year was present in a context of social isolation. This diachronic analysis of the communicational decisions of a specific outreach project allows us to find the patterns that define the centrality of its symbolic link with the territory, regardless of factors that could be considered central but, in contexts of crisis, may be secondary. The objective of this work is to identify the communicational actions with the stages and consequent possibilities that the project has throughout its history, which makes it possible to identify fixed and variable actions/motivations in the action in the territory. The results make it possible to abstract logics of potential applicability in the generality of extension projects.